Multi Akad dalam Transaksi Paylater: Tinjauan Maqashid Syari’ah terhadap Fatwa MUI dan Darul Ifta’ Mesir Serta Implikasinya Pada Preferensi Gen Z Muslim di Indonesia - Rifa, Saadatu Mukarromatil Arifah; Anugrah, Yuli Dwi Yusrani; Ichfan, Hoirul (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to examine the phenomenon of “multi-contract” (multi akad) in paylater transactions from the perspective of maqāṣid al-sharī‘ah, while comparing the legal opinions (fatwas) issued by the Indonesian Ulema Council (MUI) and Egypt’s Dar al-Ifta’ al-Misriyyah. The research also explores the implications of these fatwas for the financial preferences and consumption behavior of Muslim Generation Z in Indonesia and Egypt. Methodologically, this study employs a qualitative descriptive–comparative approach through fatwa documentation analysis, literature review on maqāṣid al-sharī‘ah, and surveys and interviews with Gen Z respondents from both countries. The findings reveal that paylater contracts often involve elements of riba (usury), gharar (uncertainty), and potential exploitation, thus failing to fully realize the objectives of maqāṣid al-sharī‘ah such as the protection of wealth (ḥifẓ al-māl), justice (‘adl), and public welfare (maṣlaḥah). Regarding fatwa perspectives, MUI emphasizes that the paylater mechanism itself is not inherently problematic; rather, the issue lies in the interest-based contracts that constitute riba. Meanwhile, although Dar al-Ifta’ has not issued a specific fatwa on paylater services, its methodological approach emphasizes wasatiyyah (moderation) and maqāṣid-based reasoning in legal determinations. The survey results indicate that Muslim Gen Zs in both countries demonstrate growing sharī‘ah awareness, yet remain open to adopting paylater services as part of the digital lifestyle. Differences in regulatory and fatwa contexts lead to distinct preferences: Indonesian Gen Z tends to be more cautious toward interest-bearing paylater schemes, while Egyptian Gen Z is more influenced by perceived benefits, technological access, and levels of Islamic financial literacy. The study concludes by emphasizing the need for sharī‘ah-based financial education and digital literacy aligned with maqāṣid al-sharī‘ah, as well as the development of compliant paylater models for Muslim Gen Zs in the digital era. This research contributes theoretically to the discourse on Islamic digital finance contracts and provides practical insights for policymakers, financial institutions, and fintech developers to design fair and maṣlaḥah-oriented paylater products.